A human centred approach to digital technologies in health care delivery among mothers, children and adolescents - Yasini Haroun; Richard Sambaiga; Nandini Sarkar; Ntuli A. Kapologwe; James Kengia; Jafary Liana; Suleiman Kimatta; Johanita James; Vendelin Simon; Fatma Hassan; Romuald Mbwasi; Khadija Fumbwe; et al. (BMC, 2022)
Abstract Background: Healthcare outcomes in child, adolescent and maternal in Tanzania are poor, and mostly characterised by fragmentary service provision. In order to address this weakness, digital technologies are sought to be integrated in the milieu of health as they present vast opportunities especially in the ability to improve health information management and coordination. Prior to the design and implementation of the Afya-Tek digital intervention, formative research was carried out to ensure that the solution meets the needs of the users. The formative research aimed to examine: the burden of disease and related health seeking behaviour; workflow procedures and challenges experiencing healthcare actors; adolescent health and health seeking behaviour; and lastly examine technological literacy and perceptions on the use of digital technologies in healthcare delivery. This paper therefore, presents findings from the formative research. Methods: The study employed exploratory design grounded in a qualitative approach. In-depth interview, focus group discussion, participant observation and documentary review methods were used for collecting data at different levels. The analysis was done thematically, whereby meaning was deduced behind the words which the participants used. Results: Findings suggest that the perceived burden of diseases and health seeking behaviour differ across age and social group. Multiple work-related challenges, such as lack of proper mechanism to track referrals and patient's information were noted across healthcare actors. There was a keen interest in the use of technologies shown by all study participants to improve care coordination and health outcomes among health system actors. Participants shared their views on how they envision the digital system working. Conclusion: The formative research provided insightful background information with regard to the study objectives. The findings are used for informing the subsequent phases of the co-development and implementation of the Afya-Tek digital health intervention; with a view to making it relevant to the needs of those who will use it in the future. As such, the findings have to a large extent met the purpose of the current study by envisaging the best ways to design digital intervention tailored to meet the needs of those who will be using it.